2018
DOI: 10.1016/j.psychres.2018.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Towards a reliable repeated-measures beads task for assessing the jumping to conclusions bias

Abstract: The jumping to conclusions bias (JTC), in which some people gather less information than others before making a decision, has been linked to delusions in psychosis. JTC is usually identified via the beads task, in which a sequence of beads (the "target" sequence) is used to measure the amount of evidence participants require before making a decision. Yet, despite its common use, the reliability of the task has never been properly investigated. We investigated its reliability, and tested an alternate version wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Thus it becomes more difficult to explain the different results about the PDI score’s effect on JTC obtained by different studies by simply pointing to the difficulty of the tasks. Also, research has shown that there are several problems with the standard usage of the bead task (McLean et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus it becomes more difficult to explain the different results about the PDI score’s effect on JTC obtained by different studies by simply pointing to the difficulty of the tasks. Also, research has shown that there are several problems with the standard usage of the bead task (McLean et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The task is not usually repeated as participants may become aware that the sequences are predetermined, masking their true reasoning styles. However, future studies could use a distractor version of the task (e.g., McLean, Mattiske, & Balzan, 2018) which may conceal the predetermined nature of the task, preserving participants’ reasoning styles. This would allow for greater reliability in assessing for over-adjustment, and comparability between the beads and BADE tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Two main variables are assessed: the number of beads drawn before a decision is made, and the proportion of extreme responders (i.e., subjects who make a decision based on one or two beads) ( Dudley et al, 2016 ). Common variations of the beads task include changes in the ratios or in the jar contents ( Dudley et al, 2016 ), altering impulsive decision; or inclusion of distractor sequences ( McLean et al, 2018 ), improving reliability and repeatability ( McLean et al, 2018 ). In a meta-analysis, people with psychosis in comparison with healthy controls required less beads to make a decision and had a higher number of extreme responders.…”
Section: Behavioral Measures Of Impulsivitymentioning
confidence: 99%